Topical beta‐blockers in dermatologic therapy. Issue 4 (21st June 2021) - Filoni, Angela; Ambrogio, Francesca; De Marco, Aurora; Pacifico, Alessia; Bonamonte, Domenico
Abstract: An increasing use of beta‐blockers in dermatology has been described over the last 10 years, despite the fact that their use in diseases other than infantile hemangiomas is off‐label. This review discusses the emerging role of topical beta‐blockers in the treatment of infantile hemangioma, but also pyogenic granuloma, Kaposi sarcoma, wounds and nail paronychia. Data in literature demonstrate that topical beta‐blockers are a safe and valid therapeutic option in numerous cutaneous diseases. Side effects are mainly restricted to the application site. Further studies and randomized trials may contribute to reinforce the role of topical beta‐blockers in the dermatological armamentarium.